Analisis Pengetahuan, Sikap, dan Kesediaan Warga terhadap Pengelolaan Sampah Rumah Tangga di Dusun Popongan - Wahid Walidi; Philein Yustitia Saraswati; Alfi Na’imatul Imtihanah; Elisabeth Imbik; Heru Subaris Kasjono; Sri Haryanti; Choirul Amri (LPPM Universitas Harapan Bangsa Purwokerto, 2026)
Household domestic waste remains an environmental issue, particularly in the management of organic waste that has not been utilized optimally. This community service activity aimed to improve community knowledge, attitudes, and willingness in waste management through the application of the open windrow composting technique in Popongan Hamlet, Mlati District, Sleman Regency, Special Region of Yogyakarta. The method used consisted of counseling activities followed by evaluation through pretest and posttest questionnaires. The results showed an increase in community knowledge into the good category after the counseling was conducted. Community attitudes toward waste management also changed in a more positive direction. Statistical analysis indicated significant differences before and after the counseling in both knowledge and attitude variables. In addition, the community demonstrated a high level of readiness to support composting activities both individually and collectively. This counseling activity was considered effective in improving community understanding of environmentally based waste management.